PERCOBAAN PENDAHULUAN PETRO - PROTEIN (VITON) SEBAGAI BAHAN MAKANAN TERNAK SAPI POTONG 1) 1972 - 1973 - SOEKANTO, SOEKANTO; SOEJONO, M.; WINOTO, WINOTO; SURISDIARTO, HARYO; SUTRISNO, JOKO (Fakultas Peternakan UGM, 1973)
-